Student understanding of soil classification using the Simplified guide to soil taxonomy - Kerschen, Kim (Kansas State University, 2014)
Soil Taxonomy is the official soil classification system used in the United States and many other countries. Any soil in the world can be classified from the order to the family level using a set of classification keys that are currently in an eleventh edition. The classification system is quite complex and can be too complicated for beginning soil science students to understand and use. Thus, a national advisory working group of the National Cooperative Soil Survey developed an abbreviated guide called the Simplified Guide to Soil Taxonomy. The goal of the simplified guide is to help reduce the complexity of soil taxonomy and aid in the classification of soils from the order to the great group level. The purpose of this study was to evaluate the effectiveness of the simplified guided when used by students in soil science courses to classify soils as compared to traditional methods using the more detailed keys. Classes at Kansas State University were used in the study and included the laboratory sections of AGRON 305 (Soils) and AGRON 515 (Soil Genesis and Classification). Student learning was evaluated using pre and post-test scores, assignments, and evaluation surveys. Results from the fall and spring semesters of AGRON 305 vary based on pre and post test scores and the assignment. Written evaluations indicated that both methods were easy to understand, especially as the lab progressed, but students responded more favorably to the abbreviated descriptions of taxa, pictures, and hyperlinks associated with the simplified guide. The Simplified Guide to Soil Taxonomy can be used in introductory soils courses. However, it is more suited for mid to upper level soil science courses, such as AGRON 515, where students responded favorably to the shorter and more comprehensible descriptions of taxa at the order, suborder, and great group level.
Keywords: Soil taxonomy; Student learning; Agronomy (0285)